A review of the bee pollination research on temperate zone crop plants in the past decade: results and the need of further studies - Benedek, P. (International Journal of Horticultural Science, 2002)
Intense research was made on the pollination of cultivated crop plants in the temperate zone region during the past decade. Some 400 publications appeared on the subject and some additional 150 papers on the effect of pesticides to the most important pollinating insects, the honeybee and the wild bees. Progress of knowledge is discussed in this paper based on the most important publications. Most new results relate to field crops and deciduous fruit species and much less to field vegetables and small fruits. Great effort was taken to improve insect pollination of crops grown under cover. All these are connected to the utilization of the honeybee as a pollinating agent and much less to native or managed wild bees. However, a number of questions arose partly from the results of latest pollination research and partly from practical experiences in commercial plant production. These indicate several research tasks to understand and to solve the problems possibly in the near future. The questions concentrate on the effectiveness of bee visits in the pollination of individual crop plants and their different cultivars and on the reliable estimate of the overall amount of bees as well as on the control of bee density during the flowering periods of crops for optimal, controlled pollination in the changing environment of agricultural crop production.